Evaluation of the Influence of Tanacetum vulgare Extract on Cognitive Functions and Hippocampal BDNF Expression - Borislava Lechkova; Michaela Shishmanova-Doseva; Niko Benbassat; Reneta Gevrenova; Pepa Atanassova; Nadya Penkova; Lyudmil Peychev; Petar Hrischev; Zhivko Peychev; Stanislava Ivanova (Molecules)
Tanacetum vulgare L. has been traditionally applied as a remedy for headaches, rheumatism, digestion, respiratory and neurological problems, and other medical conditions. However, the literature data on its effects on cognitive function are scarce. The aim of the present work was to evaluate the effects of two doses of T. vulgare alcohol extract on cognitive functions, hippocampal brain-derived neurotrophic factor (BDNF) expression, and organ toxicity in rats. Rats were treated with T. vulgare 200 mg/kg (TV 200) and 1000 mg/kg (TV 1000) for 28 days. After one week of pre-treatment, the animals were subjected to a series of tests. We found that in the active avoidance test, only TV 200 improved learning and memory, while in the passive avoidance test, both doses facilitated these processes. In addition, the two doses enhanced spatial memory. In the elevated plus maze test, only the higher dose of TV 1000 resulted in anxiolytic-like behavior. Both doses of the extract significantly increased the hippocampal expression of BDNF. We suggest that increased neurotrophic factor expression could be one of the important mechanisms underlying the cognition-enhancing effects of T. vulgare extract.